The potential use of indigenous nickel hyperaccumulators for small-scale mining in The Philippines - E S Fernando; M O Quimado; L C Trinidad; A I Doronila (Journal of Degraded and Mining Lands Management, 2013)
Uptake of nickel and three other heavy metals (copper, cobalt, and chromium) was examined in 33 species of the common and rare native vascular plants growing in an ultramafic area currently subjected to mining in Zambales Province, Luzon, Philippines. Leaf tissue samples were initially screened in the field using filter paper impregnated with dimethylglyoxime (1% solution in 70% ethyl alcohol) and later analyzed by atomic absorption spectroscopy. One species was found to be a hypernickelophore (>10,000 µg/g), eight species were nickel hyperaccumulators (>1,000 µg/g), nineteen species were hemi-accumulators (>100-1,000 µg/g), and five species were non-accumulators (<100 µg/g). This paper significantly adds to the list of hyperaccumulator species first reported for the Philippines in 1992. The findings will be discussed in context of using indigenous species for post mining ecological restoration and nickel phytoextraction in small-scale mining in the Philippines